Implementation of Differentiated Learning Based on Student Literacy Mapping in Madrasah Ibtidaiyah Terpadu As Salam Ambon - M Sahrawi Saimima; N Thati Kaplale; Bidar Sangkala; Nurhasanah Nurhasanah; Hilaluddin Hanafi (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
Differentiated learning is one of the approaches developed in the implementation of the Independent Curriculum to accommodate the diversity of students' abilities, interests, and learning needs. In the madrasah environment, the application of differentiated learning is important because students have different levels of learning readiness, especially in literacy skills. This study aims to analyze the implementation of differentiated learning based on mapping students' literacy skills in Madrasah Ibtidaiyah Terpadu As Salam Ambon and then identify the obstacles faced by teachers in its implementation. The research approach used is qualitative, with a descriptive type of research. Data were collected through in-depth interviews, observations, and documentation of selected classroom teachers using purposive sampling techniques. The results of the study show that the implementation of differentiated learning begins with a diagnostic assessment to map students' literacy skills in the categories of recognizing letters, reading syllables, reading fluently, and understanding the content of reading. The mapping results are used as the basis for classifying students and adjusting the content, processes, and learning products according to the learning needs of each student. The obstacles faced by teachers include limited time in preparing differentiated learning tools, the preparation of media and teaching materials that are in accordance with various levels of student ability, and the management of learning in heterogeneous classrooms. So that the efforts made are the need to improve teacher competence through training, the development of teachers' creativity in making learning media, school support in the provision of learning facilities, and the preparation of teaching materials that are in accordance with the needs and level of students' abilities.